Identifikasi Isolat Bakteri Termofilik dari Sumber Air Panas Lejja, Kabupaten Soppeng - Mahmudah, Rafiah; Baharuddin, Maswati; Sappewali, Sappewali (Al-Kimia, 2016)
Identification of bacterial isolates local termofilik at hot springs is the first step of a series of studies of the exploration and utilization of indigenous bacteria an area. This research aims to know the bacterial isolate bacteria from the genus termofilik in the hot springs at Soppeng Lejja and know the optimum incubation time and temperature on the growth of bacterial isolates termofilik from hot springs, Soppeng Regency Lejja. The methods used in the study include the creation of media, rejuvenation, the identification of isolates of bacteria. Bacterial identification to genus level based on Bergey’s Manual of Determinative Bacteriology are done with different test, namely: gram staining test, oxidation test, fermentation test, carbohydrates test, SIM test, TSIA test, Mr/Vp test, citrat test and urea test. The results showed that bacterial isolates identified as termofilik in the genus Pseudomonas sp, which is a gram-negative, rod-shaped cells against oxidation test, positive, negative and red metyl test against a test fermentation. indol, motility, citrate, urea and the production of H2S.